Recent advances in controlled and modified atmosphere of fresh produce - Falagán, Natalia; Terry, Leon A. (Johnson Matthey Plc, 2018)
World trade has transformed food retailing and driven the development of technology for the transportation and storage of horticultural products, providing year-round supply of fruit and vegetables. Horticultural produce is highly perishable, as fruit and vegetables continue their metabolic processes that lead to ripening and senescence after harvest, making them ultimately unmarketable. Advanced postharvest technologies are essential for reducing food waste while maintaining high standards of safety and quality. Together with cold storage, controlled atmosphere (CA) and modified atmosphere packaging (MAP) have been applied to alter the produce’s internal and external environment, decreasing its metabolic activity and extending shelf-life. Both CA and MAP have benefitted from technological innovation. Respiratory quotient control has improved the management of conventional and recently developed CA systems; gas scavengers have made MAP more efficient; and the inclusion of natural additives has enhanced food safety across the supply chain. This paper critically reviews the application of new postharvest techniques to manipulate gaseous environments and highlights areas that require further study.